2016
DOI: 10.4103/1319-3767.187607
|View full text |Cite
|
Sign up to set email alerts
|

New combined parameter of liver and splenic stiffness as determined by elastography in healthy volunteers

Abstract: Background:The diagnosis of chronic liver disease (CLD) leading to fibrosis, cirrhosis, and portal hypertension had witnessed dramatic changes after the introduction of noninvasive figure accessible tools over the past few years. Imaging techniques that are based on evaluation of the liver stiffness was particularly useful in this respect. Acoustic radiation force impulse (ARFI) emerged as an interesting figure tool with reliable repute and high precision.Aims:To evaluate liver stiffness measurement (LSM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…In individuals whose spleen dimensions were high, the spleen stiffness values were higher but this did not show statistically any significant difference. Similar to this study there are also other studies reporting that did not detect any relation between spleen stiffness and dimensions 8,11,15,16 . In their studies, Guiffré et al reported that they looked at the average spleen stiffness according to the spleen bipolar diameter and spleen area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In individuals whose spleen dimensions were high, the spleen stiffness values were higher but this did not show statistically any significant difference. Similar to this study there are also other studies reporting that did not detect any relation between spleen stiffness and dimensions 8,11,15,16 . In their studies, Guiffré et al reported that they looked at the average spleen stiffness according to the spleen bipolar diameter and spleen area.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike this study, these two studies detected slightly higher values in men compared to women but statistically, this was not found meaningful. Yet, Kassym et al, by using ARFI in their study that they evaluated the relation between the rate of the spleen stiffness values of healthy individuals and their age, gender, spleen dimensions, ethnicity and obesity, similar to this study, they determined that the spleen stiffness was higher in women than men but differently from this study, these higher values were found statistically meaningful 15 . It was estimated that this difference resulted from the number of the population which was more than this study population.…”
Section: Discussionsupporting
confidence: 54%
“…A study of healthy children and adolescents concluded that gender influences elastography at the spleen[ 43 ]. The influence of BMI on spleen shear wave velocity was not clear according to other research groups[ 21 , 33 , 44 ]. The influence of abdominal wall thickness on shear wave velocities has not yet been clarified[ 17 , 19 , 20 , 26 ] and this parameter was not assessed in our study.…”
Section: Discussionmentioning
confidence: 87%
“…This was not possible for the Philips device (p-SWE). Most of the available studies could not prove any gender-specific influence on the shear wave velocities[ 21 , 35 , 42 , 44 ]. A study of healthy children and adolescents concluded that gender influences elastography at the spleen[ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the overall values of liver and spleen shear wave velocity in these two groups, values in the unfavorable prognosis group was significantly higher than in the favorable prognosis group. This demonstrates that there is a potential relationship between liver and spleen shear wave velocity and the prognosis of patients with portal hypertension[ 9 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%